Hey so I was wondering how to differentiate $(e^2)^x$ without using the chain rule.

I tried but I always end up using the chain rule in this case.

Would appreciate some help! (No hints please).

  • 3
    $\begingroup$ I'm confused. You want help, but you don't want hints? $\endgroup$ – Y. Forman Jun 12 '18 at 14:06
  • 1
    $\begingroup$ Hint: Consider its Maclaurin series. $\endgroup$ – poyea Jun 12 '18 at 14:07
  • 1
    $\begingroup$ Use the limit definition and properties of $e$. Sorry if this is a hint. $\endgroup$ – Randall Jun 12 '18 at 14:08
  • $\begingroup$ Forman, if you are confused as to why someone needs help but doesn’t want hint answers, then maybe its not for you. $\endgroup$ – user549904 Jun 12 '18 at 14:17
  • $\begingroup$ user549904, if you think other people should do your work and you cannot deal with just hints, maybe math is not for you. $\endgroup$ – Torsten Schoeneberg Jun 12 '18 at 14:20

Indeed, using the chain rule is certainly the easiest: $$f(x)=e^{2x}\to f'(x)=2e^{2x}$$

You could however, use the product rule: $$f(x)=(e^2)^x=e^xe^x$$ Then $p=q=e^x$, and $p'=q'=e^x$

Product rule is $f'(x)=p'q+q'p\to e^xe^x+e^xe^x=2e^{2x}$

Or the quotient rule can also be used: $$f(x)=(e^2)^x=\frac{e^x}{e^{-x}}$$ Then $p=p'=e^x$, $q=e^{-x}\to q'=-e^{-x}$

Quotient rule is $f'(x)=\frac{p'q-q'p}{q^2}\to\frac{e^xe^{-x}-e^x(-e^{-x})}{e^{-2x}}=\frac{2}{e^{-2x}}=2e^{2x}$


If you know the rule

$$(a^x)'=\ln a\,a^x$$ then

$$((e^2)^x)'=\ln e^2\,(e^2)^x=2(e^2)^x.$$




Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.